2014
DOI: 10.1159/000369308
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Kidney Transplantation on Sleep, Melatonin, Circadian Rhythm and Quality of Life in Kidney Transplant Recipients and Living Donors

Abstract: Background: Sleep disturbance is an important medical problem in patients with end-stage renal disease. It might be related to the disruption of the body's circadian clock since nocturnal levels of its key biomarker melatonin are markedly reduced. We aimed at investigating whether a change in renal function due to kidney transplantation or donation would modify sleep, melatonin levels, circadian rhythmicity, and quality of life in kidney transplant recipients (KTR) and living donors (LD). Methods: In KTR, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
(38 reference statements)
1
19
0
1
Order By: Relevance
“…However, melatonin levels in control subjects were similar to those in the intervention group, and behaviorally the patients showed significant statistical improvement as a result of melatonin. These results are in agreement with other studies (Russcher et al 2015). In the latter case, the authors also did not observe beneficial effects on sleep quality due to melatonin-mediated improvement of renal function after transplantation; conversely, in an unpublished claim, kidney transplantation was associated with a rise of melatonin levels and an improvement in sleep quality due to the recovery of organ function (M Russcher, B C P Koch, C A J M Gaillard, J E Nagtegaal & P M Ter Wee, unpublished observations).…”
Section: Kidney Transplantationsupporting
confidence: 94%
“…However, melatonin levels in control subjects were similar to those in the intervention group, and behaviorally the patients showed significant statistical improvement as a result of melatonin. These results are in agreement with other studies (Russcher et al 2015). In the latter case, the authors also did not observe beneficial effects on sleep quality due to melatonin-mediated improvement of renal function after transplantation; conversely, in an unpublished claim, kidney transplantation was associated with a rise of melatonin levels and an improvement in sleep quality due to the recovery of organ function (M Russcher, B C P Koch, C A J M Gaillard, J E Nagtegaal & P M Ter Wee, unpublished observations).…”
Section: Kidney Transplantationsupporting
confidence: 94%
“…Melatonin amplitude and melatonin rhythm have been shown to decrease in chronic kidney disease patients with advancing renal dysfunction (Koch et al, 2010). There is only one study of 23 RTx recipients with saliva melatonin measurements at preTx and 3 months post-Tx (Russcher et al, 2015). Although melatonin values were low in this study, the DLMO was always calculable.…”
Section: Discussionmentioning
confidence: 54%
“…In cross‐sectional studies, the quality of sleep seems better in RTX patients compared to dialysis patients . To our knowledge, only one longitudinal study has assessed sleep with polysomnography in renal patients in the transition from dialysis to transplantation , while there is no study exploring self‐perceived quality of sleep. Cross‐sectional studies have shown that patients who have received a renal graft have less sleep apnoea and reduced PLMD .…”
Section: Introductionmentioning
confidence: 99%